Sustainable harvesting of tree bark - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
Forestry research is discovering and communicating better techniques for harvesting medicinal bark, to prevent trees dying.